Até quando? O tempo por trás das grades : uma análise das estratégias dos adolescentes frente à indeterminação temporal da medida socioeducativa de internação - Débora Cecília Ribeiro Costa (2019)
In cases of imprisonment of adolescents, the Statute of the Child and Adolescent indicates only the maximum duration - namely, three years - and does not present temporal indications for the different infractions. This dissertation aims to understand how the temporal uncertainty regarding the extent of deprivation of liberty is experienced and represented by the adolescents, in order to investigate how such perceptions interfere in the situational definition built during the period of reclusion. In order to respond to the problem of this study, first, an overview of Minas Gerais was made, based on a quantitative analysis of times of reclusion in this state. There was a statistical correlation between longer guarding times and homicide crime, as well as for younger adolescents. As a result, the semi-structured interviews conducted with the adolescents confined in Belo Horizonte were interpreted, revealing how the temporal indetermination encourages adolescents to try to accelerate their withdrawal by constructing strategies aimed at the end of detention. The adolescents signaled compliance with the measure from a process of rationalization, in an attempt to control intramural time.